Determination of Cyclopropane Fatty Acids in Food of Animal Origin by 1H NMR. (1st April 2018) - Lolli, Veronica; Marseglia, Angela; Palla, Gerardo; Zanardi, Emanuela; Caligiani, Augusta
Abstract : Cyclopropane fatty acids (CPFAs) are unusual fatty acids of microbial origin, recently detected in milk and dairy products. CPFAs have been demonstrated to be interesting molecular markers for authentication of dairy products obtained without ensiled feeds. Moreover, they can also be recognized as a new secondary component of human diet. Information is lacking on the presence of cyclic fatty acids in other food sources. Cyclopropane fatty acids have been detected by GC-MS analysis in cheese and other animal fats in concentration ranging from 200 to 1000 mg/kg fat, but in some cases, the complex fatty acid profile and the possible presence of interfering peaks make the separation not straightforward and the quantification uneasy. Therefore, a new reliable 1 H NMR method was developed to detect and measure CPFA content in different foods of animal origin, based on the detection of the characteristic signals of cyclopropane ring. The 1 H NMR (600 MHz) method showed detection limits comparable with those of full scan GC-MS, and it allowed the identification and quantitation of the cyclopropane fatty acids in different foods.